Evaluation of Human Basic Movement Systems Based on Artificial Intelligence (Texas Journal of Multidisciplinary Studies, 2022)
One of the fastest growing areas today is artificial intelligence. This article gives a brief overview of the assessment of human locomotor systems based on artificial intelligence. Today, information technology is developing rapidly in our lives.